2016
DOI: 10.1186/s12891-016-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, double-blind, randomized controlled trial of treatment of atlantoaxial instability with C1 posterior arches >4 mm by comparing C1 pedicle with lateral mass screws fixation

Abstract: BackgroundC1 posterior arch screw placement is one of the most effective treatments for atlantoaxial instability (AAI), which can be performed by either pedicle or lateral mass screw fixation. This study attempted to compare the feasibility and clinical outcomes of C1 pedicle with lateral mass screw fixations for treatment of AAI with C1 posterior arches >4 mm.MethodsA total of 140 patients with AAI (C1 posterior arches measuring >4 mm) was enrolled in this single-center, randomized, double-blind trial. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, as opposed to the lateral mass screw, far more frequent and more severe complications may be seen. The C1 pedicle screw technique is a difficult technique to implement requiring experience and it brings along a higher risk of vertebral artery injury because of its close proximity (42). In this series of ours, we used C1 lateral mass screw, we tried to place bicortical screws as much as possible, but we used unicortical screws in cases which we deemed more suitable as a result of the assessments we made.…”
Section: █ Discussionmentioning
confidence: 99%
“…However, as opposed to the lateral mass screw, far more frequent and more severe complications may be seen. The C1 pedicle screw technique is a difficult technique to implement requiring experience and it brings along a higher risk of vertebral artery injury because of its close proximity (42). In this series of ours, we used C1 lateral mass screw, we tried to place bicortical screws as much as possible, but we used unicortical screws in cases which we deemed more suitable as a result of the assessments we made.…”
Section: █ Discussionmentioning
confidence: 99%
“…In addition, improved biomechanical attributes of pedicle screws may not be of pertinent detail to this potentially frail demographic, limited in their daily activities. In the study by Yan et al, 13 outcomes were reported only in the immediate postoperative period, highlighting more cases of pain and numbness associated with lateral mass screws. The presence of immediate pain can easily be explained by the fact lateral mass screw placement requires soft tissue dissection to be extended until the far lateral margin of the facet is identified.…”
Section: Lateral Mass Screwmentioning
confidence: 99%
“…Group A had significantly shorter surgical times and blood loss as compared with group B ( P <0.01) 13. In addition, 13 (18.6%) patients in group B had burst bleeding from the C1–C2 venous plexus and 9 (12.9%) patients had immediate pain and numbness in the occipitocervical region because of C2 nerve root irritation, with no such complications experienced in group A (pedicle screw) 13. Residual neurological deficit is of great concern, as it may precipitate falls, and readmission in spondylotic patients.…”
mentioning
confidence: 92%
See 2 more Smart Citations